Description of the First Four Zoeal Stages of Grapsus albolineatus (Decapoda: Brachyura: Grapsidae) of the Red Sea Reared under Laboratory Conditions - E. Al Haj , Ahmed (Journal of King Abdulaziz University: Marine Sciences, 2022)
Larvae of Grapsus albolineatus (Latreille, in Milbert, 1812) of the Red Sea were reared in the laboratory for 24 days and four zoeal stages were obtained. In this paper, these first four zoeal stages of Grapsus albolineatus have been described for the first time; these descriptions aid to compare this species with other congeneric species and to show that its morphological features are basically equal to those defined for grapsid zoeae. Cephalothorax lateral spines are present from the second zoeal stage, however, a third seta on the second segment of the endopod of the first maxilliped in the fourth zoea is observed for the first time in a grapsid four zoea and the diagnostic value of this character needs to be investigated further.